PLANT MAINTENANCE PERFORMANCE MEASUREMENTS SHORTFALLS - Koloane, Sello David (The South African Journal of Industrial Engineering, 2022)
Modern industry is faced with huge challenges in the 21st century. One the most pressing issues is poor plant performance, which erodes shareholders’ return-on-investment. Despite enormous investment in production plants, high availability continues to be unattainable. The critical review research methodology adopted for this study was based on a literature review and guided by the plant life cycle framework. It was also informed by the notion that plant failures do not only originate in the operational phase. The results indicate that some plant items failed before operation could be initiated, and that performance indicators were inadequate and ineffective. Plant availability instruments did not report on the health of the standby plants, even though designers had seen the need to have redundancy ready at all times. All of the identified shortfalls will be tested in the system dynamics maintenance model that will be developed in the future.